2016
DOI: 10.3390/nu8110684
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Gluten-Induced Gut Dysbiosis Is Accompanied by Selective Upregulation of microRNAs with Intestinal Tight Junction and Bacteria-Binding Motifs in Rhesus Macaque Model of Celiac Disease

Abstract: The composition of the gut microbiome reflects the overall health status of the host. In this study, stool samples representing the gut microbiomes from 6 gluten-sensitive (GS) captive juvenile rhesus macaques were compared with those from 6 healthy, age- and diet-matched peers. A total of 48 samples representing both groups were studied using V4 16S rRNA gene DNA analysis. Samples from GS macaques were further characterized based on type of diet administered: conventional monkey chow, i.e., wheat gluten-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 87 publications
1
47
0
Order By: Relevance
“…It was also shown that increased presence of some of the bacterial species involved in gluten metabolism leads to enteritis [13]. Our group recently demonstrated that Streptococcaceae and Lactobacillaceae families were enriched in GS rhesus macaque model of CD, while Coriobacteriaceae predominated in healthy animals [14]. In the future, studies to elucidate speciic dysbiotic pathways that distinguish NCGS from CD need to be done.…”
Section: Composition Of Host Gut Microbiome and Ncgs/cdmentioning
confidence: 93%
See 4 more Smart Citations
“…It was also shown that increased presence of some of the bacterial species involved in gluten metabolism leads to enteritis [13]. Our group recently demonstrated that Streptococcaceae and Lactobacillaceae families were enriched in GS rhesus macaque model of CD, while Coriobacteriaceae predominated in healthy animals [14]. In the future, studies to elucidate speciic dysbiotic pathways that distinguish NCGS from CD need to be done.…”
Section: Composition Of Host Gut Microbiome and Ncgs/cdmentioning
confidence: 93%
“…It has been reported that bacteria involved in gluten metabolism predominantly belong to phylum Firmicutes, in particular, those from the genus Lactobacillus, followed by Streptococcus, Staphylococcus, and Clostridia [13,14]. Recently, it was shown that GFD treatment signiicantly altered proportions of these bacterial groups and that restoration of normal bacterial lora took many months and possibly years [14,15].…”
Section: Composition Of Host Gut Microbiome and Ncgs/cdmentioning
confidence: 99%
See 3 more Smart Citations